Hooliganism as a problem of public order in the Ukrainian SSR in the early 1950s - V. A. Grechenko (Law and Safety)
The article examines the topical and insufficiently studied in historical and legal science issue of the factors that caused hooliganism in the early 1950s, the level of this type of crime in the main regions of Ukraine at that time and some steps taken by the Ministry of Internal Affairs of the Ukrainian SSR to reduce hooliganism. Hooliganism occupied one of the main positions in the list of offences committed by young people. The factors of hooliganism had their roots in the years of war and post-war devastation, which were the childhood and adolescence of the majority of those who committed crimes under the relevant article “Hooliganism” of the Criminal Code of the Ukrainian SSR.